Lectotypifications, new synonyms and new occurrences of Dalechampia L. (Euphorbiaceae) in Brazil - Mendes, Jone Clebson Ribeiro; Secco, Ricardo De S.; Bigio, Narcisio C.; Rosário, Alessandro S. (Phytotaxa, 2019)
Three new occurrences of Dalechampia are reported, D. brownsbergensis, D. attenuistylus and D. heterobractea, of which one is a new record for Brazil. Dalechampia uleana and D. brevipedunculata are synonymized. The holotype of D. hastata is updated and lectotypes are designated for D. juruana. For the names D. cujabensis and D. magnoliifolia, a second-step lectotype are respectively designated. Morphologically similar taxa and the geographic distribution of each species are discussed. Recommendations for updating the list of Euphorbiaceae species for the Flora of Brazil 2020 project are also provided.